Non-imaging microwave and millimetre-wave sensors for concealed object detection - Kapilevich, Boris Y.; Harmer, Stuart W.; Bowring, Nicholas J. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Technology now allows the use of microwave and millimeter wave sensors for the detection of concealed objects, typically weapons and explosive devices, on the human body. This book discusses these developments and includes examples of actual devices built and tested by the authors. Topics include active millimeter wave sensor using the direct detection approach and the heterodyne approach, active microwave sensor for CNR-based object detection, passive millimeter wave sensors, and the role of shielding effects in operating non-imaging MM-wave sensors'--
1. Introduction -- 2. Background and theory -- 3. Active millimetre-wave sensor using direct detection approach -- 4. FMCW sensors for detecting hidden objects -- 5. Active microwave sensors for complex natural resonance-based object detection -- 6. Passive millimetre-wave sensors -- 7. The role of shielding effects in operating non-imaging sensors.
Includes bibliographical references (pages 200-202) and index.
Keywords: Scanning systems; Metal detectors; Explosives -- detection; Microwave detectors